2018
DOI: 10.1111/ijtd.12137
|View full text |Cite
|
Sign up to set email alerts
|

The impact of learner characteristics on training transfer expectation: a survey of Thai teachers’ perception of cloud computing tools

Abstract: Researchers and practitioners have spent much time on and given a great deal of attention to the practical characteristics of professional development and its delivery in an attempt to understand the training transfer problem at the workplace. However, when we consider the individual employee as the primary agent of the transfer process, we cannot and should not ignore their perceived self‐rated attributes, motivation and expectations of learning and transfer at the pre‐training stage. In this study, it is hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…training design) or individual variables (e.g. learner characteristics) when studying self‐regulated learning in the workplace (Celestin & Yunfei, ). For instance, training design has been contemplated in many learning transfer theories (Baldwin & Ford, ; Holton et al , ) and has been shown to play an important role in promoting transfer motivation (Velada et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…training design) or individual variables (e.g. learner characteristics) when studying self‐regulated learning in the workplace (Celestin & Yunfei, ). For instance, training design has been contemplated in many learning transfer theories (Baldwin & Ford, ; Holton et al , ) and has been shown to play an important role in promoting transfer motivation (Velada et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the Spanish context (Renta-Davids et al , 2014), it was found that insofar as the training courses were related to the workplace activities and the professional development of the participants, they positively influence the transfer of training. In the educational context, the work of Celestin and Yunfei (2018) showed that the personal characteristics of a teacher (preparation for learning, effectiveness of personal transfer, motivation for transfer, personal capacity and perceived validity of content) in the pre-training stage are significant predictors of the performance expectation of the transfer effort in the post-training stage. Additionally, whether other variables of a qualitative nature moderate the relationships proposed in the model could be analysed – for instance, whether there are differences that depend on the size of the schools, the level of education offered at the school or the location of the school (Lazarenko and Shamarica, 2019).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Motivation to transfer, one of the core LTSI constructs, is “the trainees’ desire to use the knowledge and skills mastered in the training program on the job” (Noe, 1986 , p. 743) and is considered to be a key factor for the transfer of training (Holton et al, 2000 ; Burke & Hutchins, 2007 ; Gegenfurtner et al, 2009 ; Massenberg et al, 2017 ). Motivation to transfer plays the mediating role between other LTSI factors and actual learning transfer (Gegenfurtner et al, 2009 ; Hutchins et al, 2013 ; Nafukho et al, 2017 ; Celestin & Yunfei, 2018 ; Yaghi & Bates, 2020 ). The most influential factor in predicting actual training transfer of school innovation by the in-service teachers was their motivation to transfer (Dreer et al, 2017 ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%